(untitled) - Block, Daniel I.; (1943-...) (U.S.A, 2017)
Designed for the pastor and Bible teacher, the Zondervan Exegetical Commentary on the Old Testament brings together commentary features rarely gathered together in one volume. With careful discourse analysis and interpretation of the Hebrew text, the authors trace the flow of argument in each Old Testament book, showing that how a biblical author says something is just as important as what they say. This volume was previously published in the Hearing the Message of Scripture series.
Keywords: the Hebrew Bible